Epidemiology of foot injuries using National Collegiate Athletic Association data from the 2009-2010 through 2014-2015 seasons - Lievers, W. B.; Goggins, K. A.; Adamic, P. (Journal of Athletic Training, 2020)
Context: Researchers analyzing data from the National Collegiate Athletic Association Injury Surveillance Program have not considered the differences in foot injuries across specific sports and between males and females.